Inclusive education in context: Reflections upon the implementation of the decree 1421 of 2017 - Díaz-Piñeres, Alexandra; Bravo-Rueda, Carolina; Sierra Delgado, Gloria Esperanza (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2020)
Taking into account the importance of the processes of inclusive education in the Colombian context and how the incorporation of new practices preceded by the diffusion of the norm, can generate conflicts within the educational community, the objective of this work was to analyze the challenges and opportunities that the institutions face in the implementation of Decree 1421 of 2017 of the Ministry of Education of Colombia, it was developed in a rural public school in the department of Santander through a technical-pedagogical support. The problem addresses the school exclusion regarding the difficulties of implementing the norm that guide the care of people with disabilities within the framework of inclusive education. The research was carried out under the qualitative methodological approach, descriptive and experimental, of a research-practical action type. There was applied the discourse analysis based on the dimensions for the institutional improvement of policies, practices, and culture. The process allowed the identification of factors that can facilitate or can hinder the provision of a quality of service for all, minimizing the problem of exclusion and making easier the construction of institutional processes in an updated way. This research concludes that to face the challenges and opportunities that arise on the path of inclusive education, the systematized accompanying processes and adapted to the context, developed during enough period of time and lead for the members of communities impact directly in the educational system, developing new dynamics and reforms to be part of, the stay and quality of all students.